Reframing the Relations between State and Religion in Post–War Bosnia: Learning to be Free!. Issue 1 (2nd January 2017) - Alibašić, Ahmet; Begović, Nedim
Abstract: Since the collapse of Communism, and especially following the devastating war of the early 1990s, efforts to reach political consensus in Bosnia and Herzegovina have proved extremely difficult. State–church relations have in principle evaded such a destiny. Key to this has been the general, even if not always fully functional, acceptance of freedom of religion and equality as the main framework for resolving dilemmas involving the role of religion and religious practice. The state, religious entities and society at large have undergone a process of accommodating themselves to a liberal model of state–church relations, which was introduced as part of the post–war constitutional settlement. This article analyses the different stages and vicissitudes of such an accommodation by focusing on the evolution of the legal framework for religious freedom and equality as well as its actual implementation in practice.